Price Distortions in Capital Markets and Corporate Employment—A Theoretical and Empirical Analysis Based on Microdata - Zheng, Jinfeng; Wang, Wenbo; Ji, Zhaoxia; Wang, Wentao; Li, Xiaodong (Journal of Behavioral Economics and Policy, 2026)
Employment, as the cornerstone of societal well-being, is a critical economic issue that concerns the immediate interests of the general public and the broader national development. However, existing research has generally overlooked the significant role that factor input prices play in the employment process of enterprise employees. Therefore, based on data from the China Industrial Enterprises Database, this paper focuses on examining the impact of capital price distortions on enterprise employee employment. The study finds that capital price distortions suppress firms’ labor demand and reduce their spending on employee training, which is detrimental to both employment and the improvement of employee quality. In terms of the transmission mechanism, capital price distortions increase firms’ returns on capital, thereby generating a substitution effect of capital for labor, and suppress labor demand by reducing firms’ production efficiency. In terms of firm heterogeneity, the negative impact of capital price distortions on employee employment is more pronounced in capital-intensive firms, firms not receiving government subsidies, large-scale firms, state-owned enterprises, and export-oriented firms. These findings indicate that national policies prioritizing the improvement of factor market price determination mechanisms and employment training subsidies are of great significance for promoting labor employment and reducing fluctuations in the labor market.